Maternal Serum Nitric Oxide Levels in Adolescent Pregnancies - Hasan Onur Topçu; Ali İrfan Güzel; Kuntay Kokanalı; Sabri Cavkaytar; Dilek Uygur; Salim Erkaya (Gynecology Obstetrics & Reproductive Medicine)
OBLECTIVE: We aimed to evaluate maternal serum nitric oxide (MSNO) levels in adolescent pregnancies. STUDY DESIGN: A total of forty five pregnancies were included to the study, of these eight were adolescent pregnancies (age range, 18-19 years old). Factors analyzed between adolescent pregnancies and reproductive age pregnancies (age range 20-35 years old) were; age, gravidity, parity, gestational weeks, umbilical and middle cerebral artery Doppler velocimetry values, birth weigts, APGAR 5. minute scores and MSNO levels. Statistical analyses were carried out by using the statistical packages for SPSS 15.0 for Windows (SPSS Inc., Chicago, IL, USA) with Chi-square (χ2) test and Student’s t test. The receiver operator characteristic (ROC) curve analysis was used to establish the cutoff values for MSNO levels. RESULTS: Demographic and clinical characteristics showed no statistically significant difference among the groups (p>0.05). MSNO levels were statistically significantly lower in adolescent age pregnancies.                                               CONCLUSION: According to current study, MSNO levels were statistically significantly different from reproductive age pregnancies. MSNO levels may be a discriminative marker in adolescent age pregnancies but further studies with larger participants are needed to get more definite results.